Analisis Kesulitan Siswa Dalam Menyelesaikan Operasi Hitung Aljabar Bentuk Pecahan - Januarvi, Endit Donistyara, Masduki, S.Si.,M.Si (2016)
ABSTRACT Endit Donistyara Januarvi/A410120171. ANALYSIS OF STUDENT DIFFICULTIES IN COMPLETING THE OPERATION ARITHMETIC ALGEBRAIC FRACTIONS. Essay. Faculty of Teacher Training and Education, Muhammadiyah University of Surakarta. May, 2016. This research aimed to describe the error and difficulties of students and find out the factors causing of students have difficulty in solving algebraic operations form of fractions. This research is a qualitative descriptive. Subjects of this research is 6 students taken from class VII A and VII B at SMP Muhammadiyah 8 Surakarta. The data collection technique using the test method, interviews, observation and documentation. Data analysis technique conducted in three stages of data reduction, exposure data, and conclusions or verification. The analysis was developed based on three types of errors are errors on the concept, the principle of error, and errors in completing the operation. So it can is known any difficulties experienced by students in solving algebraic operations form of fractions. The result showed that most difficulties experienced by many students is the difficulty in principle, where it appears that the student made a mistake in a matter of fractions algebra associated with the multiplication of two algebra with two tribes. Contributing factor is that students do not understand the rules as well as the properties in solving algebraic operations form of fractions. Keywords: concept, difficulties, fractions algebra, operations, principle